Anselms Geschöpflichkeitsbeweis - Knauer, Peter (Zeitschrift für katholische Theologie, 2010)
According to common opinion, Anselm of Canterbury wanted to deduce the existence of God from the concept of God as the one »in comparison to whom nothing greater can be thought«. But at the same time he claims that God is »greater than all that can be thought«. So he himself already denies the possibility of a direct concept of God. In reality he underlines that God plus the world are not more than God, and this is directly a statement about the world. Its being and its being created are formally identical. If it is possible to think of the world as »entirely related to... / in total distinction from... «, it must be thought of in this way.